Factors Contributing To Customer Complaints In PCR (Professional Commercial Radio) Software R&D: A Case Of Motorola Solutions Penang - N.Kasavan, Shobana Menon; Khew, Ying Ye; K.A. Ahamed Meeran, Hamid Kareem (2014)
Customer complaints naturally reflect customer dissatisfaction. From a business perspective, customer complaints are a sign indicating the presence of problems that needs to be resolved at the soonest possible time. Uncovering what is causing the customer complaints presents an opportunity to improve a firm’s business growth. Motorola Solutions primarily receive three types of complaints from customers: [1] feature functioning but not fulfilling customer’s expectation, [2] feature malfunction and [3] long cycle time to fix issues. In order to root-cause the underlying factors that causes customer complaints,the SVP Framework was adopted as the research methodology.